Different power modes of microwave ablation for hepatocellular carcinoma: Evaluation of recurrence rate and factors related to recurrence - Tiantian Dong; Fang Nie; Ting Liu; Lan Wang; Dan Yang; Xueliang Yan (Asian Journal of Surgery, 2023)
Purpose: To evaluate the safety and efficacy of different power modes(constant power and variable power) percutaneous microwave ablation (MWA) for treating hepatocellular carcinoma (HCC) and to predict the risk factors of recurrence after MWA. Materials and methods: In this retrospective study, a total of 112 patients with solitary HCC were included from January 2015 to January 2021. All patients received MWA through a percutaneous approach that was guided by ultrasound, 45 patients received variable power MWA, and the remaining 67 were treated with constant power MWA. The complete ablation rates, local recurrence rates, complications, and short-term survival were analyzed. Possible risk factors for tumor recurrence were analyzed. Results: The complete ablation rates were 95.9% for the first ablation and 100% for the second ablation for ≤3 cm lesions. The complete ablation rates were 84.2%(95.9% versus 84.2%, p = 0.039) for the first ablation and 94.7% (100% versus 94.7%, p = 0.113) for the second ablation for 3–5 cm lesions. Local and distant recurrence rates were 18.7%(21/112) and 14.3%(16/112). The 1-, 2-year survival rates were 86.3 and 66.3%, respectively. Subgroup analysis showed that 1-, 2-year survival rates were 91.1% and 78.5% in ≤3 cm group, and were 74.4% and 40.9% in 3–5 cm group, respectively. Univariate analysis revealed that a positive correlation existed between the HBV DNA replication(p = 0.007), AFP level of pre-MWA(p = 0.001) and post-MWA(p<0.001), tumor diameter(p<0.001), irregular shape(p = 0.014), proximity to the risk location(p = 0.008), poor differentiation(p = 0.003), constant power(p = 0.028), length(p<0.001) and width of ablation zone(p = 0.001), and present complication(p<0.001), and early recurrence. Multivariate analysis identified HBV DNA replication(OR = 0.266, p = 0.036), AFP level of pre-MWA (OR = 4.001, p = 0.036), tumor diameter (OR = 2.153, p = 0.042), tumor location (OR = 0.910, p = 0.046), and width of ablation zone(OR = 2.530, p = 0.044) were independent prognosis factors causing postoperative HCC recurrence. Conclusion: Variable power MWA of HCC appears to be a safe and effective treatment. HBV DNA, AFP level of pre-MWA, tumor diameter, tumor location, and width of ablation range appear to be independent predictors of tumor recurrence.